(Benzyldiphenylphosphane-1jP)-[l-bis(diphenylphosphanyl)methane-2:3j2P:P0]nonacarbonyl- 1j3C,2j3C,3j3C-triangulotriruthenium(0) - Shawkataly, Omar; Ahmed Khan, Imthyaz; Sirat, Siti Syaida; Rosli, Mohd Mustaqim (International Union of Crystallography, 2014)
The asymmetric unit of the title compound, [Ru3(C19H17P)(C25H22P2)(CO)9], consists of two independent molecules. The bis(diphenylphosphanyl)methane ligand bridges an Ru—Ru bond and the benzyldiphenylphosphane ligand binds to the third Ru atom. The Ru—Ru bond cis to the benzyldiphenylphosphane ligand is the longest of the three Ru—Ru bonds in both molecules. In the crystal, molecules are linked by C—H O hydrogen bonds, forming layers parallel to the ac plane. C—H contacts further stabilize the crystal packing.